THE TRANSFORMATION OF ISLAMIC ELEMENTARY SCHOOLS IN MALANG WITHIN THE TRADITIONAL ISLAMIC EDUCATION IN THE MILLENNIAL ERA - Muhammad Walid (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
Changes in Islamic elementary schools (as known as madrasah ibtidaiyah) are a response to the strong demands and pressures in the world of education today. The increasingly open competition encourages madrasah ibtidaiyah to change the direction of its learning and management model, which is no longer top-down, but more accommodating. This research was conducted at MIN Malang 1 and MIN 2 Druju Malang Regency. Research conducted between 2018-2019 involved many informants, including the head of the madrasa, deputy head of the madrasa, teachers, educational staff, and guardians of students. The data used as the basis for analysis are the results of observations, interviews, and documentation studies. From the data analysis, it was found that changes in madrasah ibtidaiyah occurred not only in the curriculum aspect, but also in institutional management in general. This allows madrasah ibtidaiyah to compete with other educational institutions because they have adopted an interactive-accommodative education system by juxtaposing two kinds of education; religion and general. This study confirms that the changes that occur in madrasah ibtidaiyah are not only aimed at increasing competence so that they are able to compete openly with various existing educational institutions, but also in order to show themselves as the main choice of students in obtaining knowledge that is not limited to religious knowledge. However, changes like this have the opportunity to forget the substance of the change itself, namely the presence of a new form of education that is more accommodating and responsive. Therefore, a madrasah ibtidaiyah management model is needed that is able to respond to scientific and social challenges comprehensively in the future.